2018
DOI: 10.21815/jde.018.065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Evidence‐Based Dentistry Workshops on Educators’ Use of Evidence in Teaching and Practice: A Pilot Study

Abstract: The aims of this pilot study were to evaluate the short-term impact of evidence-based dentistry (EBD) workshops on educators' use of clinical evidence in their clinical practice and educational activities and to identify barriers they encountered in implementing evidence in their teaching and clinical practice. Between April 2012 and January 2014, a series of EBD workshops was delivered to 31 dental faculty members and postdoctoral students at three Canadian dental schools. Survey I, assessing participants' pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Experiences of implementation of an EBD curriculum throughout a 4-years period have been successfully reported, with dental students and faculty members becoming increasingly aware and supportive of using the EBD model in daily practice 19,20 . Other study reported improved skills from faculty members to critically appraise evidence and implementation of the model in their practices after a set of workshops based on recommendations of the American Dental Association (ADA) 9 . When it comes to teaching EBD elements, multifaceted educational interventions have been shown to improve the overall competence and confidence of health students towards EBP 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiences of implementation of an EBD curriculum throughout a 4-years period have been successfully reported, with dental students and faculty members becoming increasingly aware and supportive of using the EBD model in daily practice 19,20 . Other study reported improved skills from faculty members to critically appraise evidence and implementation of the model in their practices after a set of workshops based on recommendations of the American Dental Association (ADA) 9 . When it comes to teaching EBD elements, multifaceted educational interventions have been shown to improve the overall competence and confidence of health students towards EBP 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Although most dental faculty members acknowledge the importance of teaching EBD, barriers such as time, knowledge, and resources have been indicated in the process to successfully implement EBD in the dental curriculum 8 . Also, criticism and resistance to change of the current teaching practice have been recognized as barriers originated by part of the faculty members, along with the claim that it is difficult to convince people about the existence of evidence on a particular topic 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] When dental instructors have been involved as stakeholders in research, the literature has mostly focused on assessing their knowledge and attitudes regarding EBCM. [18][19][20] Studies suggest that practitioners experience a lack of knowledge of EBCM, 18,19 face time limitations for its implementation, deal with resistance from other practitioners, and have challenges in transitioning their current practice models. 20,21 To our knowledge, there remains limited evidence on dental instructors' perceptions on the overall implementation of EBCM in dental education.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Studies suggest that practitioners experience a lack of knowledge of EBCM, 18,19 face time limitations for its implementation, deal with resistance from other practitioners, and have challenges in transitioning their current practice models. 20,21 To our knowledge, there remains limited evidence on dental instructors' perceptions on the overall implementation of EBCM in dental education. Furthermore, there is a lack of evidence on how clinical instructors experience the complex changes in the cariology curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation